2022
DOI: 10.1142/s0192415x22500665
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Mechanistic Models Reveal the Neuroprotective Effects of Diterpene Ginkgolides against Astrocyte-Mediated Demyelination via the PAF-PAFR Pathway

Abstract: Currently, therapies for ischemic stroke are limited. Ginkgolides, unique Folium Ginkgo components, have potential benefits for ischemic stroke patients, but there is little evidence that ginkgolides improve neurological function in these patients. Clinical studies have confirmed the neurological improvement efficacy of diterpene ginkgolides meglumine injection (DGMI), an extract of Ginkgo biloba containing ginkgolides A (GA), B (GB), and K (GK), in ischemic stroke patients. In the present study, we performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…For management of AIS patients within 4.5 hr from the symptom onset, intravenous rt-PA was approved, and researchers reported that the combination of GDLI and rt-PA was superior to rt-PA alone for clinical efficacy, supporting add-on effects of GDLI in thrombolytic therapy on AIS (Zhao et al, 2022) signaling pathways (Liu et al, 2019;Zhang et al, 2018). Recently, researchers found that the neuroprotective activities of GDLI were related to its regulation of the sphingolipid and neurotrophin signaling pathways via gene set enrichment analysis (GSEA) (Wang et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For management of AIS patients within 4.5 hr from the symptom onset, intravenous rt-PA was approved, and researchers reported that the combination of GDLI and rt-PA was superior to rt-PA alone for clinical efficacy, supporting add-on effects of GDLI in thrombolytic therapy on AIS (Zhao et al, 2022) signaling pathways (Liu et al, 2019;Zhang et al, 2018). Recently, researchers found that the neuroprotective activities of GDLI were related to its regulation of the sphingolipid and neurotrophin signaling pathways via gene set enrichment analysis (GSEA) (Wang et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, GDLI could significantly decrease rat neurological deficit scores, reduce brain infarct volume, and protect against cerebral ischemia–reperfusion damage by activating both Akt/Nrf2 and Akt/CREB signaling pathways (Liu et al, 2019; Zhang et al, 2018). Recently, researchers found that the neuroprotective activities of GDLI were related to its regulation of the sphingolipid and neurotrophin signaling pathways via gene set enrichment analysis (GSEA) (Wang et al, 2022). As the main active components of GDLI, GB was reported to possess multiple neuroprotective mechanisms including antiinflammation, antiexcitotoxicity, antiapoptosis, and the blood–brain barrier (BBB) protection; and the neuroprotective strategies of GK involved antioxidation, mitochondrial protection, elevation of autophagy via upregulation of the AMPK/mTOR/ULK1 signaling pathway, and promotion of neurogenesis by activating JAK2/STAT3(Xu et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ginkgo diterpene lactone meglumine (GDLM) is made of extracts from ginkgo biloba L, composed of the active ingredients of ginkgolides A, B, and K, and some other contents. It has been widely used in the treatment of ischemic stroke in China . The active ingredient in GDLM has been shown to have a variety of neuroprotective and reparative effects that can help maintain the blood-brain barrier; reduce brain edema; improve energy metabolism; help with antioxidation, anti-inflammation, and antiapoptosis; and promote angiogenesis .…”
Section: Introductionmentioning
confidence: 99%